Teacher educators' attitudes toward computers: a study among teacher educators in teacher'-training colleges in Johor, Malaysia - Ridzuan, Abang Ahmad; Hong, Kian Sam; Ahmad, Aliza (Penerbit UTM Press, 2001)
Teachers shoulder the heavy responsibility of ensuring that students experience a meaningful learning environment. Information and communication technologies, in general, and computers, in particular has been put forward as a strategic tool for enhancing these learning environments. Teacher educators, as frontliners of the teacher preparation process, should themselves be well versed in the fields of integrating computers into the learning processes. Teacher educators who use computers regularly and have positive attitudes towards computers it is hoped, will rub on some of their knowledge, skills and enthusiasm to future teachers who will enter the school system. The purpose of this study is to determine the level of computer use and attitude towards computer among teacher educators. Differences in computer use among teacher educators based on selected demographic data are also investigated. This study also looks at the relationship between attitude towards computers, namely liking, confidence and anxiety with computer use for educational purposes among teacher educators. A questionnaire was designed to obtain the necessary demographics, levels of computer use and attitudes of the sample toward computers. The Computer Attitude Scale by Lyod and Gressard was used to measure the attitudes toward computers. The sample consisted of 224 teacher educators at three teacher-training colleges in Johor, Malaysia. Findings indicate that the teacher educators used computers moderately in the course of their work. Teacher educators mostly used the computers for preparing exercises and examination questions. Computer assisted instruction was seldom utilized. Teacher educators without experience in using computers exhibit significantly less computer use as compared to those with more than a year of computer use experience. In general, the teacher educators have positive attitudes and low anxiety toward using computers for teaching and learning. The three attitude domains (liking, confidence and anxiety) were significantly related to computer use. Confidence and liking were positively related to computer use while anxiety was negatively related to computer use.